Improving the Students’ Reading Ability at the Eighth Grade Students of SMP Negeri 5 Polut through Running Record Method (A Classroom Action Research) - Andi Mangnguntungi Sudirman (Ethical Lingua: Journal of Language Teaching and Literature, 2016)
This research is a classroom action research that focused on improving the students’ reading ability through Running Record Method. Two cycles had been conducted, where each cycle consisted of four meetings. It employed reading test as instrument. A number of subjects of the research were 30 students conducted of 11 women and 19 men. At diagnostic test, the average of students’ score in determine main ideas and contents of reading ability before implementation Running Record Method is poor (50.75), but after implementation Running Record Method in cycle I the assessment of their reading ability improves (60.44), is greater than diagnostic test. This means there is an improvement of the students’ reading ability. But, this is classified as fairly, so the researcher decides to organizer in cycle II. Assessment of cycle II is greater than from cycle I (72.89 > 60.44) it classified as good which means there is improvement of the students’ reading ability.